Agronomic performance of Stylosanthes guianensis cv. Pucallpa in the American tropical rain forest ecosystem - Amézquita, María Cristina; Toledo, José M.; Keller-Grein, Gerhard (1991)
The purpose of this study is to define the range of adaptation of Stylosanthes guianensis CIAT 184, released in 1985 as cv. Pucallpa by IVITA (Instituto Veterinario de Investigaciónes Tropicales y de Altura) and INIPA (Instituto Nacional de Investigación y Promoción Agropecuaria) in Peru. Data from 32 RIEPT (International Network for Tropical Pastures Evaluation) type B trials conducted in the American humid tropics between Mexico and Bolivia were used for this study. The study shows that cv. Pucallpa is tolerant to anthracnose under a wide range of soil, climate and locations; the cultivar is better adapted to low altitudes (< 850 m.a.s.l.), on soils that are acid (pH < 5.0), which have low levels of organic matter (< 3.4%), are moderately sandy (18–56% sand), and which have rainfall accumulated in 12 weeks > 800 mm. At higher altitudes (> 1000 m.a.s.l.), the cultivar appears to respond to higher levels of organic matter.